Executive Committee Minutes 2019-08-22 - Academic Senate:::::::::
Agenda approved. Minutes of 5/9/19 approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Refer to Committee: Honors at Graduation Policy and transfer students – not referred. From EPC: Governance structure for approval of overlays and for assessment of GE – referred to S&F. APARC Report. EPC Report. FSAC Report. SAC Report. Senate Agenda approved.